Constant product markets

$$$$(R_alpha - Delta_alpha) (R_beta + gamma * Delta_beta) == k

Constant product markets

$$$$maximize m_p * Delta_alpha - Delta_beta(subject to) Delta_alpha,

Delta_beta >= 0(R_alpha - Delta_alpha) (R_beta + gamma * Delta_beta)

== k

Constant product markets

$$$$gamma * m_p <= m_u <= gamma**(- 1) * m_p

Constant product markets

$$$$(R_alpha - Delta_alpha) (R_beta + gamma * Delta_beta) == k

Constant product markets

$$$$maximize m_p * Delta_alpha - Delta_beta(subject to) Delta_alpha,

Delta_beta >= 0(R_alpha - Delta_alpha) (R_beta + gamma * Delta_beta)

== k

Constant product markets

$$$$gamma * m_p <= m_u <= gamma**(- 1) * m_p

Constant product markets

$$$$(R_alpha - Delta_alpha) (R_beta + gamma * Delta_beta) == k

Constant product markets

$$$$maximize m_p * Delta_alpha - Delta_beta(subject to) Delta_alpha,

Delta_beta >= 0(R_alpha - Delta_alpha) (R_beta + gamma * Delta_beta)

== k

Constant product markets

$$$$gamma * m_p <= m_u <= gamma**(- 1) * m_p